PERKEMBANGAN KARAKTER OH YI YOUNG DALAM DRAMA RESIDENT PLAYBOOK: PERSPEKTIF PSIKOLOGI SASTRA - Nuraini, Syafira Priyo; Zaini, Zaini (Multikultura, 2026)
Literary works are not only expressed in written form but also in audiovisual media such as films and television dramas, one of the most popular manifestations of the Korean Wave (Hallyu) being K-drama. This study aims to analyze the character development of Oh Yi Young in the drama Resident Playbook using a literary psychology approach by applying Sigmund Freud’s psychoanalytic theory on the dynamics of the id, ego, and superego. The research employs a qualitative descriptive method, with primary data consisting of dialogue, scenes, and interactions within the drama, and secondary data drawn from academic literature to support the analysis. The findings indicate that Oh Yi Young’s character development progresses from the dominance of the id, characterized by impulsivity and escapism in response to pressure, toward the emergence of the ego as reflected in the ability to assess reality rationally, and ultimately reaches the superego through ethical actions, professional commitment, and the internalization of moral values in emergency situations.